Behavioral Intention Mahasiswa dalam Penggunaan ERP - z, annisa hakim (Program Studi Akuntansi FPEB UPI, 2019)
Abstract. This study examined the external factors of education and training on TAM with three research models, namely the relationship of education and training to perceived usefulness and perceived ease of use; the relationship perceived ease of use towards perceived usefulness; and the relationship perceived ease of use and perceived usefulness to behavioral intention. The research sample was students who took the SAP Finance in semester 20182019 as many as 163. The research model was analyzed using Structural Equation Model variant base with SmartPLS 2.0. The results of the study stated that education and training had a significant effect on perceived usefulness and perceived ease of use, perceived ease of use had a significant effect on perceived usefulness, and perceived ease of use had a significant effect on behavioral intention. Only the perceived usefulness does not significantly effect on the behavioral intention to use ERP system. This might be due to the respondents being students who do not have experience in the world of work so that they are less aware of the benefits to the system that is used in real terms.Keywords. Behavioral Intention; Education and Training; Tecnology Acceptance Model (TAM).Abstrak. Penelitian ini menguji faktor eksternal pendidikan dan pelatihan terhadap TAM dengan tiga model penelitian, yaitu hubungan pendidikan dan pelatihan terhadap perceived usefulness dan perceived ease of use; hubunganÂ perceived ease of use terhadap perceived usefulness; dan hubungan perceived ease of use dan perceived usefulness terhadap behavioral intention. Sampel peneitian ini adalah mahasiswa yang mengambil matakuliah SAP Keuangan semester ganjil 20182019 sebanyak 163. Model penelitian dianalisis menggunakan Struktural Equation Model berbasis varian (SEM) dengan SmartPLS 2.0. Hasil penelitian menyatakan bahwa pendidikan dan pelatihan berpengaruh secara signifikan terhadap perceived usefulness dan perceived ease of use, perceived ease of use memiliki pengaruh signifikan terhadap perceived usefulness, dan perceived ease of use memiliki pengaruh signifikan terhadap behavioral intention. Hanya perceived usefulness yang mempengaruhi tidak signifikan terhadap behavioral intention sistem ERP. Hal ini mungkin disebabkan responden adalah mahasiswa yang belum memiliki pengalaman di duni kerja sehingga kurang merasankan manfaat terhadap sistem yang digunakan secara nyata.